Predictors of Poor Long-Term Outcomes in Patients with Newly Diagnosed Asymptomatic Cardiac Sarcoidosis: A Cardiovascular Magnetic Resonance Study - Nicoleta Nita; Dominik Felbel; Rima Melnic; Michael Paukovitsch; Wolfgang Rottbauer; Dominik Buckert; Johannes Mörike (Biomedicines)
Background: The prevalence of patients with cardiac sarcoidosis (CS) diagnosed at a subclinical stage has increased; however, their long-term outcomes are not well known. Objectives: To investigate the incidence and predictors of adverse long-term outcomes in newly diagnosed patients with asymptomatic CS. Methods: Forty-three patients with newly diagnosed asymptomatic CS and comprehensive baseline evaluation with cardiovascular magnetic resonance (CMR) were studied. Asymptomatic CS was defined as CS in patients with biopsy-proven extracardiac sarcoidosis without cardiac symptoms but with abnormalities on CMR or positron emission tomography according to Heart Rhythm Society criteria. The primary endpoint was a composite of all-cause mortality, new ventricular arrhythmia or an atrioventricular block requiring cardiac device implantation, and hospitalization for heart failure. Results: Patients had a mean age of 56 ± 11 years and presented with normal left ventricular (LV) ejection fraction (58 ± 4%). A total of 44.2% of patients reached the composite endpoint during 5 years of follow-up. Patients with the primary endpoint were predominantly female (73.7%) and had a significantly higher prevalence of right ventricular (RV) involvement compared to patients without the primary endpoint (RV late gadolinium enhancement (LGE) in 26.3% vs. 4.2%, p = 0.037). In multivariate regression analysis, extensive LV LGE (HR 1.61, 95% CI 1.16–2.04, p = 0.004) and impaired RV global longitudinal strain (GLS) at baseline (HR 0.46, 95% CI 0.24–0.68, p = 0.015) were significantly predictive of the primary endpoint, whereas treatment with corticosteroids after CS diagnosis was significantly associated with improved outcomes (HR 7.69, 95% CI 1.11–11.11, p = 0.044). Conclusions: Newly diagnosed patients with asymptomatic CS have a significant incidence of adverse outcomes after 5 years of follow-up. The extent of LV LGE and impaired RV GLS at baseline predict poor long-term outcomes in asymptomatic CS.